Comparison of loneliness levels in visually impaired from different sports branches - (:unkn) unknown (Kamla-Raj Enterprises, 2016)
The present study is aimed at both, to determine loneliness levels of the visually handicapped athletes from different branches and to compare loneliness levels of the athletes playing and not playing sports. Three hundred-forty visually handicapped athletes, consisting of 280 visually handicapped male athletes participating in goalball, B1, B2-B3 Futsal, Track and Fields and Judo competitions within the 2011-2012 season activity program of Turkey for the Blind Athletics Championships and 60 visually handicapped athletes who did not take part in any sport branches, were included in the research. The Personal Information Form was prepared to obtain personal data of those visually handicapped ones who participated in the research. Besides, the UCLA Loneliness Scale was used to determine their loneliness states. As a result, statistically, a significant difference was determined between sport branches like goalball: 56.07±8.33 score, Track and Fields: 50.35±5.45 score, Futsal: 52.85±6.43 score, Judo: 50.58±4.43 score and loneliness points. © Kamla-Raj 2016.
Keywords: Athletes; Loneliness; Sports; Visually impaired